Offshoring via vertical FDI in a long-run Kaleckian model - Ryan Woodgate (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2022)
This paper develops a two-country Kaleckian model in which "Northern" firms invest a fixed fraction of total investment in foreign affiliates in the low-wage "South" in order to offshore the production of intermediate goods over time and lower overall labour costs. On the back of this setup follows an analysis of the macroeconomic implications of offshoring in the short and long run. Offshoring through vertical FDI is found to lead to a falling wage share and a simultaneously falling price level and rising mark-up in the North, whereas the effect on equilibrium capacity utilisation may be positive or negative. Interestingly, however, regardless of the effect on capacity utilisation and firm profitability, we can show that the structural change implied by offshoring leads to lower rates of capital accumulation and employment in the North relative to the initial (pre-offshoring) values in the short run. The long-run effects on Northern employment and growth, on the other hand, depend crucially on the long-run accumulation rate of the Northern-owned multinational firms. However, the model shows that, if wages endogenously converge during the transition due to higher unemployment in the North and lower unemployment in the South, then the long-run Northern capacity utilisation and accumulation rates are increasingly likely to fall relative to pre-offshoring values. The model appears well suited to shed light on many real-world macroeconomic phenomena, such as rising FDI flows, falling wage shares, rising mark-ups in an era of low inflation, hysteresis, and secular stagnation.
Keywords: F62; F23; O41; E11; E12; 330; offshoring; foreign direct investment; distribution; stagnation